Improving water competency among children on the autism spectrum: the AquOTic randomized controlled trial - Kemp, Erika; Nikahd, Melica; Howard, Mequeil; Darragh, Amy; Crasta, Jewel E. (Frontiers in Pediatrics, 2024)
Introduction: There is a critical need for evidence-based and manualized interventions targeting water competency including swim and water safety skills tailored to meet the needs of children on the autism spectrum, a group that is at a high risk of drowning. This study examined the efficacy of AquOTic -a 10-week occupational therapy-based aquatic intervention to improve water competency among children on the autism spectrum. Clinical Trials Registration: NCT05524753. Methods: A total of 37 children on the autism spectrum (ages 5 -9 years) were randomized to a waitlist control group (n=24) or AquOTic intervention group (n=37; 28 males). Blinded assessors administered the standardized Water Orientation Test-Alyn (WOTA) 1 and 2 and a Swim Skills Checklist to all participants pre-and post-AquOTic/control. Repeated measures mixed effects models were used to examine intervention effects. Results: Average WOTA 1 scores increased significantly after participants received AquOTic (∆=5.7; 95% CI: 3.7-7.8; p<0.001), and average WOTA 2 scores increased significantly after participants received AquOTic (∆=9.0; 95% CI: 5.7-12.3; p<0.001). Average swim skills increased significantly after participants received AquOTic (∆=7.6; 95% CI: 5.3, 10.0; p<0.001). Conclusion: Our results highlight the efficacy of AquOTic to improve water competency among children on the autism spectrum. Further research is needed to examine long-term effects, dosage requirements to achieve water competency, and the impact of aquatic therapy on other health outcomes.